City Charter and Ordinances of the City of Lake Forest 88 (1894) - (:unkn) unknown (My University, 1893)
§ 88: Prohibited firing off a gun or pistol within the city limits. Violators fined not exceeding three dollars for such offense.
Keywords: DISCHARGE